2021
DOI: 10.3748/wjg.v27.i48.8283
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interactions between gut microbiota and autophagy

Abstract: A symbiotic relationship has set up between the gut microbiota and its host in the course of evolution, forming an interkingdom consortium. The gut offers a favorable ecological niche for microbial communities, with the whole body and external factors ( e.g. , diet or medications) contributing to modulating this microenvironment. Reciprocally, the gut microbiota is important for maintaining health by acting not only on the gut mucosa but also on other organs. However, failure in one or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 154 publications
(162 reference statements)
0
12
0
Order By: Relevance
“…Emerging evidence supports that the gut microbiota may contribute to liver diseases through multiple mechanisms influenced by bacterial composition [ 91 ]. The reciprocal interactions between the gut microbiota and autophagy have been well described in previous reviews [ 92 , 93 ]. In general, autophagy deficiency leads to an altered composition and diversity of the gut microbiota, resulting in dysbiosis.…”
Section: Autophagy and Gut Barrier Functionmentioning
confidence: 79%
“…Emerging evidence supports that the gut microbiota may contribute to liver diseases through multiple mechanisms influenced by bacterial composition [ 91 ]. The reciprocal interactions between the gut microbiota and autophagy have been well described in previous reviews [ 92 , 93 ]. In general, autophagy deficiency leads to an altered composition and diversity of the gut microbiota, resulting in dysbiosis.…”
Section: Autophagy and Gut Barrier Functionmentioning
confidence: 79%
“…Fusobacterium nucleatum) and gut metabolites (e.g., lipopolysaccharide, secondary biliary acids, cytokines, hormones) can modulate autophagy and thus stimulate extensive host molecular sensors (Lapaquette et al, 2021). Currently, whether polyphenols can modulate autophagy by modifying gut microbiota and microbiota-derived products to improve GLMDs has not been reported and therefore deserves further investigation.…”
Section: Intestinementioning
confidence: 99%
“…These findings reveal that polyphenols maintain intestinal homeostasis and relieve intestinal inflammation by activating autophagy. Nevertheless, it is important to note that some intestinal microflora (e.g., Lacticaseibacillus , Lactobacillus , Bifidobacterium , Butyrivibrio fibrisolvens , Megamonas , Roseburia , Desulfovibrio , Ruminococcus genus, and Fusobacterium nucleatum ) and gut metabolites (e.g., lipopolysaccharide, secondary biliary acids, cytokines, hormones) can modulate autophagy and thus stimulate extensive host molecular sensors (Lapaquette et al., 2021). Currently, whether polyphenols can modulate autophagy by modifying gut microbiota and microbiota‐derived products to improve GLMDs has not been reported and therefore deserves further investigation.…”
Section: Polyphenols and Tissue‐specific Autophagy Alterationsmentioning
confidence: 99%
“…Numerous in vivo studies suggested that gut microbiota-derived metabolites, including neurotransmitters, neuromodulator peptides, short-chain fatty acids (SCFAs), and LPSs, influence attenuating neuroinflammation [21,22]. Studies have reported that gut metabolites are vital in regulating neurodegenerative and neuroinflammatory disorders [5,23,24] by initiating autophagy [25,26].…”
Section: Introductionmentioning
confidence: 99%